Performance Study Of 1.3 Ton Slurry Ice Machine Capacity In Cold Chain Fish Handling - Dendi Haris; Dian Sutono Hs (Fakultas Perikanan dan Ilmu Kelautan Universitas 17 Agustus 1945 Cirebon, 2022)
Slurry ice is a solution to improve the quality of fish caught and cultured. The purpose of this research is to analyze and test the performance of the slurry ice machine. The analysis used includes calculating the power performance coefficient (COP), refrigeration capacity (Q), refrigerant flow rate, volume flow rate, compressor work (WComp). The heat released by the condenser and the heat absorbed by the refrigerant in the evaporator. The calculation uses data from the measurement of condenser temperature, compressor pressure. Methods to calculate the calculation of specification data and pressure from the compressor use formulas. The results showed that COP = 3.8-4.3, Qtot = 9-10 kW (for each hour), m = 0.06 kg/s, Wcomp = 2.35-2, 6 kW, Qcond = 12, 4-12.52 kW, Qevap = 9.8-10.17 kW, the total refrigeration load for 24 hours is 228 kW. The total production of slurry ice for 24 hours is 1,396.8 kg or 1.3968 Tons. The results of the test on catfish that were cooled using slurry ice, the decrease in temperature from the initial temperature of catfish 27.8°C to a temperature of (-0.7°C) took 36 minutes. Meanwhile, chilled catfish using shaved ice with an initial temperature of 27.8°C catfish to 2°C takes 1 hour.